Primary Preservice Teachers’ Drawings of Number-Based Two-Digit Addition and Subtraction - Marinšek, Miha; Hmelak , Maja (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
Whole number addition and subtraction are required topics in early-grade mathematics curricula. This study, with a sample size of N=117, introduces a unique method of using self-designed drawings to explore visual representations of mathematical concepts. The collected drawings show how preservice teachers communicate mathematical ideas, and reveal insights into their grasp of the place value concept and potential addition/subtraction teaching visual representations. Results showed that even though a significant portion of the participants demonstrated a clear comprehension of how to teach key mathematical concepts, a prominent trend emerged: about one-third of preservice teachers did not employ base ten grouping in their drawings of two-digit numbers. Similarly, one-third illustrated arithmetic operations symbolically, merely converting numbers into iconic forms, and additionally often misrepresented subtraction. These findings point to specific areas where preservice teachers’ meta-representational abilities could be improved. By emphasizing and strengthening these areas in teacher education programs, the pedagogical skills of future educators can be enhanced.